1969
DOI: 10.1136/adc.44.236.515
|View full text |Cite
|
Sign up to set email alerts
|

The metacarpal index of infants.

Abstract: Some infants appear to have long fingers, and since arachnodactyly is a feature of Marfan's syndrome, it is important to know whether a baby's long fingers are outside the normal range.In 1960, Sinclair, Kitchin, and Turner observed that arachnodactyly in Marfan's syndrome was related to the length and breadth of the metacarpal bones and showed that the metacarpal index was a useful criterion of arachnodactyly. The index is calculated by measuring the 2nd, 3rd, 4th, and 5th metacarpals. The sum of the lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…In roentgenograms, the metacarpal index in this series increased compared with that of normal controls reported by Parish (1966) and Joseph and Meadow (1969). Tatsuno et al (1983) reported the same results.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In roentgenograms, the metacarpal index in this series increased compared with that of normal controls reported by Parish (1966) and Joseph and Meadow (1969). Tatsuno et al (1983) reported the same results.…”
Section: Discussionsupporting
confidence: 79%
“…The metacarpal index was measured in 8 cases and it ranged from 7.2 to 9.4. The metacarpal index of these cases increased compared with that of normal control reported by Parish (1966) and Joseph and Meadow (1969). Spinal deformity was observed in 7 cases.…”
mentioning
confidence: 56%
“…On the proximal end of these metacarpals, pseudoepiphyses and pseudoepiphyseal notches can occur normally (most prevalent on metacarpals II and V), while Humerus and radius/ulna in a-e, hands in l-p, and femur and tibia/fibula in f-k. a Newborn. The metacarpal index is a measure of relative slenderness (Sinclaire et al 1960;Joseph and Meadow 1969;Parish 1966). b An 8-year-old.…”
Section: The Short Tubular Bones Of the Hand (Metacarpals And Phalanges)mentioning
confidence: 99%
“…In infancy before the appearance of the metacarpal epiphyses and up to about 2 years of age the index remains constant (5.2 in male; 5.5 in female infants). The index rises during childhood, reaching a peak at about 16 years of age, and then falls slightly during adult life (Walker 1979;Rand et al 1980;Joseph and Meadow 1969 The epiphyses in the hands frequently undergo minor changes in shape, size or structure, many of which occur in the general population as normal anatomical variants. One example is the occurrence of multiple centers of ossification in the proximal phalanx of the thumb.…”
Section: Radiographic Synopsismentioning
confidence: 99%